PENGARUH KEKUATAN OTOT LENGAN DAN OTOT PERUT TERHADAP HASIL FLOATING PADA CLUB BOLA VOLI PUTRA SUKUN - Yoga Pradana; Nanang Indardi; Mohammad Arif Ali (Plyometric : Jurnal Sains dan Pendidikan Keolahragaan, 2022)
This study aims to determine the effect of arm muscle strength on the results of floating serve in the Sukun men's volleyball club, Kudus Regency 2020, find out whether abdominal muscle strength affects the service results of the men's volleyball club, Kudus Regency Sukun Club in 2020, find out which is better between muscle strength arm and the influence of abdominal muscle strength from the flotation service of the Sukun Putra Volleyball Club, Kudus Regency 2020. Based on the results of research and discussion, the following conclusions can be drawn: arm muscle strength has a significant effect on the results of the 2020 PORVIT men's volleyball club flotation service, abdominal muscle strength has a significant effect on the 2020 PORVIT volleyball club float service results, arm muscle strength has a greater influence than abdominal muscle strength on floating service results at the PORVIT men's volleyball club in 2020. It is proven from the results of the t-test of arm muscle strength, a significance value of 0.000 < 0.05, t-count 5.735 > t-table 2.201 and the results of the t-test muscle strength abdomen obtained a significance value of 0.003 <0.05, t-count 3,492 > t-table 2,201.